Acidentes químicos ampliados: um desafio para a saúde pública The increase in chemical accidents: a challenge for public health - Carlos M. de Freitas; Marcelo F. de S. Porte; Carlos M. Gomez (Universidade de São Paulo, 1995)
Os acidentes envolvendo substâncias perigosas nas atividades de transporte, armazenamento e produção industrial de produtos químicos constituem um sério risco à saúde e ao meio ambiente. Objetiva-se discutir, no âmbito da saúde pública, alguns dos desafios que esses tipos de acidentes colocam, principalmente para os países de economia periférica. Através da combinação de informações quantitativas e qualitativas, foram definidos e caracterizados esses tipos de acidentes e seus diversos riscos. Esses acidentes têm se apresentado com a maior gravidade nos países de economia periférica, embora a maioria deles venha ocorrendo sem o adequado registro de informações básicas para a avaliação e vigilância, como é demonstrado no caso do Rio de Janeiro (Brasil). Além da tarefa de se avaliar as conseqüências de eventos, por vezes extremamente complexos, coloca-se também, a de formular estratégias de controle e prevenção em realidades sociais que configuram um terreno fértil para a ocorrência e agravamento dos mesmos. Chemical accidents involving explosions, large fires and leakages of hazardous substances occuring during transport, storage and industrial production of chemicals constitute a real challeng to health, environmental and industrial safety professionals. The aim of this article is to discuss the main questions that this kind of accident provokes, in terms of public helth, particularly in developing countries such as Brazil. The paper defines and characterises these accidents and the various health risk they involve excluding the leakages of hazardous substances during "normal" production in industry - through the combination of quantitative and qualitative information drawn from the international literature on the subject. From some examples of chemical accidents such as occurred in Bophal (Índia), Vila Socó (Brazil), São Paulo (México) and data of the World Health Organization (WHO), the authors seek to show that these events present a worsening, in terms of immediate deaths and injuries, in developing countries. The statistics of chemical accidents which occurred during the last ten years (1984 to 1993) in the State of Rio de Janeiro are used taken as a frame reference for the purpose of bringing to light the great number of occurrences made with no registration of basic information regarding assessment or surveillance. The complexity of causes and consequences, together with the structural problems of developing countries, present public health professionals and institutions, with some important tasks especially those os health risk assessment and the formulation of strategies to prevent and control future major chemical accidents.